SAT0586-HPR Differences in the Provision of Routine Treatment provided to Patients with Rheumatoid Arthritis in Austria, Sweden and the UK. (23rd January 2014) - Prodinger, B.; Ndosi, M.; Andreasson, I.; Persson, G.; Stamm, T.; Nordenskiöld, U.; Lundgren-Nilsson, A.
Abstract : Background: Despite the efforts toward more collaboration with patients in research and clinical practice, little is known about how the organisation of rheumatology settings differs between European countries. Objectives: This research aimed to explore from the perspectives of patients and health professionals (HPs) how treatment processes for patients with rheumatoid arthritis (RA) are set up in three Rheumatology Units across Europe. Methods: A qualitative study was conducted with patients and health professionals in Austria, Sweden and the UK. Two consecutive focus groups were conducted with patients and HP respectively at each site. Analysis was conducted in two steps: Firstly, based on the data maps were developed for each site to illustrate what happens when, who is involved and what is the role of the patient in treatment processes. Secondly, the maps from each site were compared and contrasted with the maps from the other sites. Emerging differences were put into context to elaborate on how institutional structures and arrangements shape treatment processes. Results: Twenty patients and 20 health professionals participated in 12 focus groups. While the three sites were comparable in the basic structure (being University Hospitals; offering services at an outpatient and inpatient ward, and a day clinic; supervision of services by a rheumatologist), the content and comprehensiveness of services differed. The differences impacted on the continuity within treatment, information provided to and accessible for patients, as well as communication amongst HPs. For instance, to ensure that patients are provided with and have access to adequate information, multi-modal provision of information was only provided at the SE-site. There, multi-modal information was provided by the multidisciplinary rehabilitation team within special educational sessions and the rheumatology association (Reumatikerforbundet). At the UK-site information was continuously distributed and accessible for patients through the nurses in the nurse-led clinics, as well as the information distributed through arthritis-related associations. At the AUT-site information was lacking which caused uncertainty in patients; some patients described that they seek for information on the Internet which resulted in an overwhelming amount of information causing even more uncertainty in the end. Conclusions: The main differences between the three European rheumatology settings were the accessibility to a multi-professional team, the communication amongst team-members (incl. documentation), as well as information provided to patients. This EULAR-funded study can serve as a framework for more detailed comparisons of treatment processes provided to people with RA across Europe. To optimize health care services for patients with RA, the integration of the perspectives of patients and HP is valuable given their experiences and insights from what actually works in everyday practice. Acknowledgements: This study was funded by a EULAR Health Professionals grant. Disclosure of Interest: None Declared